Perfusion, Extent, Depth, Infection and Sensation (PEDIS) classification system to assess the severity of Diabetic Foot Wounds in the Homecare setting - Sintawati majid; Juhelnita Bubun; Sri Wahyuni; Eva Arna Abrar; syaiful (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Introduction: The prevalence of diabetic foot ulcers in Indonesia is twice the global prevalence. An initial assessment of the severity of the wound is necessary to recognize early signs of skin damage and provide the right decision to begin wound treatment. The purpose of this research was to use the PEDIS classification system to assess the severity of diabetic foot Ulcers in the homecare setting. Methods: This was a quantitative descriptive study on diabetic foot ulcers patients in independent practice and homecare in Makassar City in July–October 2023. Data were collected using the PEDIS classification observation sheet which consists of perfusion measured using vascular doppler to assess peripheral artery disease in the form of a combination of waves and ABI values, extended uses the length x width, depth of skin layers involved, infection assess signs and symptoms of infection and sensation using monofilament test 10g at three points of plantar neuropathy of the foot. Results: 36 samples were found during the research period. The general severity of the injury was grade 2. Almost all patients were non- peripheral artery disease. The wound extenth was >3 cm2, and the depth of skin involved includes superficial, tendon and bone, the level of infection was limited to local infection. Almost all patients were found to experience loss of sensation in the feet. Conclusions: The PEDIS classification system can be used to assess the severity of diabetic foot ulcers in a homecare setting. However, it must be carried out by trained personnel. Keywords: degree of severity; diabetic foot ulcers; home care setting.